Pendampingan Kesehatan Dan Pemeriksaan Tensi Darah Pada Posyandu Lansia Untuk Meningkatkan Kesadaran Kesehatan Lansia - Afrizal Hasan; Khairunnisa Batubara; Shandra; Wiyanna Mathofani Siregar (Jurnal Pengabdian Keperawatan Dan Kesehatan Holistik, 2026)
Hypertension is one of the major health problems among the elderly and often goes unnoticed due to the lack of apparent symptoms. Limited routine blood pressure monitoring and low health awareness contribute to an increased risk of complications in older adults. This community service program aimed to improve health awareness among the elderly through health assistance and blood pressure screening at an elderly integrated health post (Posyandu Lansia). The program employed a promotive and preventive approach by conducting individual blood pressure measurements, health assistance, and health education related to hypertension and healthy lifestyle practices. The activity involved 30 elderly participants registered at the Posyandu. The results showed that 40% of the participants were classified as hypertensive, 33% as pre-hypertensive, and 27% had normal blood pressure levels. Evaluation of participants’ understanding indicated that approximately 80% of the elderly were able to comprehend the educational materials provided. In addition, the level of participation and enthusiasm during the activities was high. This program had a positive impact on increasing awareness of the importance of regular blood pressure monitoring and self-management of health among the elderly. Therefore, health assistance through Posyandu Lansia can be an effective strategy for early detection and prevention of hypertension in the elderly.